Seksio Sesarea Pada Kehamilan Mioma Uteri:Studi Kasus - Alfaina Wahyuni; Nusaibah Binti El-Riza (Universitas Malahayati Lampung, 2026)
ABSTRACT Uterine myomas are the most common benign tumors of the uterus in women of reproductive age. Fibroids that develop during pregnancy can cause complications during pregnancy and delivery. Myomectomy during cesarean section is generally avoided because increased vascularity of the uterus during pregnancy can lead to uncontrollable heavy bleeding and may require hysterectomy during cesarean delivery. A 38-year-old woman with a history of 3 pregnancies, 1 live birth, and 1 abortion, at 37 weeks of pregnancy, with a fetus in breech presentation and an ultrasound showing giant uterine fibroids in the lower uterine segment. An elective cesarean section was planned. Intraoperative findings included large, multiple uterine fibroids in the lower segment, requiring myomectomy. The patient received a postoperative transfusion and recovered well without other complications. Multiple giant uterine fibroids located in the lower uterine segment can be treated with a myomectomy during a cesarean section. This procedure is relatively safe for experienced obstetricians, provided they anticipate bleeding during and after the operation. Keywords: Cesarean Section, Pregnancy, Uterine Myoma. ABSTRAK Mioma uteri adalah tumor jinak paling umum pada uterus wanita usia reproduksi. Fibroid yang berkembang selama kehamilan dapat menyebabkan komplikasi selama kehamilan dan persalinan. Myomektomi saat operasi caesar umumnya dihindari karena peningkatan risiko perdarahan pasca melahirkan dan kemungkinan histerektomi saat persalinan caesar. Seorang wanita berusia 38 tahun dengan riwayat 3 kehamilan, 1 kelahiran hidup, dan 1 keguguran, pada usia kehamilan 37 minggu, dengan janin dalam presentasi sungsang dan hasil USG menunjukkan mioma uteri besar di segmen bawah uterus. Persalinan caesar elektif direncanakan. Temuan intraoperatif meliputi mioma uteri besar dan multiple di segmen bawah, yang memerlukan miomektomi sebelum melahirkan bayi. Pasien menerima transfusi pascaoperasi dan pulih dengan baik tanpa komplikasi lain. Multipel mioma uteri besar yang berlokasi di segmen bawah rahim dapat dilakukan myomektomi pada saat operasi caesar. Tindakan ini relatif aman dilakukan oleh dokter kandungan berpengalaman dengan tetap mengantisipasi terjadinya perdarahan selama dan sesudah operasi Kata Kunci: Seksio Sesarea, Kehamilan, Mioma Uteri.